Knowledge of HIV-AIDS a dominant factor of antiretroviral therapeutic adherence in women with HIV-AIDS - Surilena Surilena; Jean Valeria (Universa Medicina, 2015)
BackgroundAntiretroviral therapy adherence (ART adherence) is a factor significantly extending life expectancy of people living with HIV/AIDS. The objective of this study was determine several factors on ART adherence in women infected with HIV/AIDS. MethodsA cross-sectional study involving 99 women with HIV/AIDS who were infected through their sexual partner or spouse was conducted in Dharmais Hospital between March and August 2014. The instruments used were demographic and self-esteem questionnaires, Hamilton rating scale for depression, Hamilton rating scale for anxiety, knowledge, perception of ART benefits and limitations, family support, peer support as well as assessment of ART adherence. The knowledge questionnaire has been validated with Cronbach’s alpha = 0.823. Data were analyzed using Chi-Square test and multivariate logistic regression. ResultsA total of 99 women with HIV/AIDS participated in the study, with an age range of 30- 60 years and mean age of 36 ± 3.72 years. A total of 57.58% of participants showed poor ART adherence. Multivariate logistic regression analysis showed that knowledge, ART side effects, depression, peer support and ARV availability significantly affected ART adherence (p<0.05). The most dominant factor affecting ART adherence was knowledge, with OR = 64.02 (95% CI 4.99-670.12). ConclusionWith good knowledge about HIV/AIDS infection, ART benefits, and possible ARV side effects, women living with HIV/AIDS are expected to carry out ART adherence according to the recommended rules.